Exploring the Development of Nursing Clinical Judgment Among Students Using Virtual Reality Simulation. Issue 2 (4th March 2023) - Pardue, Karen T.; Holt, Kristen; Dunbar, Dawn-Marie; Baugh, Nancy
Abstract : Background: Virtual reality simulation (VRS) is an emerging pedagogy in nursing education. Purpose: The purpose of this qualitative exploratory study was 2-fold: to determine nursing students' learning experiences when engaged in VRS, and to explore learners' problem-solving/clinical reasoning approach after participation in a VRS clinical scenario. This article reports student descriptions of clinical reasoning/clinical judgment when considering their VRS experience. Methods: Qualitative description provided a methodological orientation for the study. Widely accepted frameworks for nursing clinical judgment provided a theoretical basis. Results: Focus group participant narratives reveal evidence about nursing clinical judgment when applied to established descriptions and phases. Conclusion: Study findings suggest that VRS experiences promote development of nursing clinical judgment among students.